Integrasi Business Process Management dalam Mewujudkan Bisnis Berkelanjutan - Fathul Bachri; Jeni Susyanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Sustainable business is a critical necessity in responding to global environmental, social, and economic challenges. Business Process Management (BPM) offers a systematic approach to designing, analyzing, and optimizing business processes in line with sustainability principles. This article aims to examine the role of BPM in promoting business sustainability through a review of recent literature. This research uses a literature review method by analyzing 25 reputable journal articles published in the last five years. The results indicate that integrating BPM with sustainability goals improves resource efficiency, reduces carbon emissions, and strengthens corporate governance. This study also reveals that BPM contributes to data-driven decision-making to support long-term sustainability strategies.